HIGH EFFICIENT BROADBAND CLASS-E POWER AMPLIFIER DESIGN USING SYNTHESIZED LOW-PASS MATCHING NETWORKS - Abubakar, N.; Musa, A.; Gidado, A. S. (FUDMA Journal of Sciences, 2023)
High-efficiency broadband Class-E power amplifiers (PAs) using high-order low-pass filter prototype is presented. A Gallium Nitride GaN transistor was used and characterized to prescribe the optimal output impedance for the broadband Class-E operation. A sixth order low-pass filter matching network was designed and implemented for the output matching. While the output provides optimized fundamental and harmonic impedances within an octave bandwidth. The simulated results show that an optimal band of operation was realized from 1.2GHz to 2GHz with an efficiency measured from 80% to 89%. An overall power amplifier bandwidth of 0.9GHz to 2.2GHz was measured between 10W to 20W output power with gain of 10dB to 13dB and efficiency was found to be around 63% to 89% throughout the band.